2019
DOI: 10.1039/c8se00499d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of glucose into 5-hydroxymethylfurfural using a bifunctional Fe3+ modified Amberlyst-15 catalyst

Abstract: In this study, a series of Fe3+ modified Amberlyst-15 resins (Fe/AR) were prepared and used as environmentally friendly bifunctional catalysts for the conversion of glucose to 5-hydroxymethylfurfural (HMF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…51,66 Besides, humins formed via HMF polymerization were also observed in the reaction for an extended amount of time which could be noticed from the darker color of the used catalyst and the product solution. 67,68 Overall, the optimal reaction time is 6 h giving 86% of glucose conversion and 72% of HMF yield, showing a signicant improvement over the typical reaction setup.…”
Section: Effects Of Reaction Setupmentioning
confidence: 93%
“…51,66 Besides, humins formed via HMF polymerization were also observed in the reaction for an extended amount of time which could be noticed from the darker color of the used catalyst and the product solution. 67,68 Overall, the optimal reaction time is 6 h giving 86% of glucose conversion and 72% of HMF yield, showing a signicant improvement over the typical reaction setup.…”
Section: Effects Of Reaction Setupmentioning
confidence: 93%
“…4. 5-Hydroxymethylfurfural is a well-known biomass-derived and versatile chemical [95] that is synthesized from glucose via a two-step process: the isomerization of glucose to fructose and then the dehydration of fructose to 5-hydroxymethylfurfural [96][97][98]. As shown in Fig.…”
Section: Production Of Hexamethylenediamine From 5-hydroxymethylfurfuralmentioning
confidence: 99%
“…The first loss within 224-327 °C may be caused by decomposition and elimination of the -SO 3 Na groups and the introduced small organic species in the materials [22], while the second loss at higher temperature of 327-448 °C may be attributed to decomposition of the support skeleton [23]. The thermal stability of referential Resin-Cu catalyst was also investigated by TG analysis (Supporting Informa-tion File 1, Figure S3), showing a high thermal stability as well [24][25][26]. The above results indicated that all prepared materials could remain stable in the system when used to catalyze organic reactions.…”
Section: Characterization Of the Prepared Materialsmentioning
confidence: 99%